Aiming at One-Stage Corrective Surgery for Extended Thoracic Aortic Dilatation - Niinimaki, Eetu; Kajander, Henri; Paavonen, Timo; Sioris, Thanos; Mennander, Ari (International Journal of Angiology, 2014)
Definitive treatment of extended thoracic aortic dilatation is a major surgical challenge. Histopathology of resected thoracic aortic wall may reveal undiagnosed aortitis affecting outcome. We sought to investigate the benefit of thorough histopathology after one-stage corrective surgery for the treatment of extended thoracic aortic dilatation. Five patients underwent one-stage corrective surgery using the hybrid open arch repair by the frozen elephant trunk together with endovascular aortic grafting. A representative sample of the resected aortic arch was procured for histology. T- and B-lymphocytes, plasma cells, macrophages, and immunoglobulin G4 (IgG4) positivity were evaluated by immunohistochemistry. The mean preoperative maximum aortic diameter was 54 mm (range, 41–79 mm). The mean follow-up was 18 months (range, 1–24 months). As confirmed by computed tomography (CT) upon follow-up, complete thrombosis of the false lumen at the level of the frozen elephant trunk was achieved in all patients with dissection. One patient was operated due to atherosclerotic dilatation of the thoracic aorta, and postoperative CT showed successful exclusion of the atherosclerotic dilatation; this 75-year-old man was diagnosed with IgG4-positive aortitis and experienced unexpected blindness after surgery without evidence of emboli or long-term neurological impairment upon repeated brain CT. The hybrid open arch repair by the frozen elephant trunk and simultaneous endovascular repair is a feasible choice for one-stage surgery through sternotomy aiming at definitive treatment of extended thoracic aortic pathology. However, systematic evaluation of inflammation may reveal concealed aortitis affecting postoperative outcome and need for long-term surveillance.
Keywords: extended thoracic aortic dilatation; IgG4; frozen elephant trunk; one-stage surgery